Effects of combined oral sucrose and nonnutritive sucking (NNS) on procedural pain of NICU newborns, 2001 to 2016: A PRISMA-compliant systematic review and meta-analysis. Issue 6 (February 2017) - Liu, Yi; Huang, Xinchun; Luo, Biru; Peng, Wentao
Abstract: Background: Both oral sucrose (OS) and nonnutritive sucking (NNS) are effective nonpharmacological methods to alleviate procedures pain in neonatal intensive care unit (NICU) newborns when they were used alone, but the combined effect of OS+NNS remains controversial. So, we conducted this study to evaluate the efficiency of NNS combined with oral sucrose on pain relief in NICU newborns undergoing painful procedures. Methods: We searched PubMed, Ovid (Medline), Embase (Medline), Cochrane Central Library, and other resources such as Google Scholar, bibliographies of included literatures for all available articles. Two reviewers screened literatures and extracted data independently. The fixed effects model was used to pool the results using Reviewer Manager (RevMan) 5.3. As each study included in our meta-analysis had been approved by Ethics Committee or institutional review board, thus our study did not need ethical approval. Results: Seven randomized controlled trials, including 599 participants, were contained in our meta-analysis. The combination of oral sucrose and NNS is associated with reduced pain scores (mean difference [MD], −0.52; 95% confidence interval [CI], −0.68 to −0.36); shortened crying time (MD, −0.92; 95% CI, −1.39 to −0.44); but the 2 groups did not differ significantly in reducing bradycardia (MD, 0.73; 95% CI, 0.32–1.68), tachycardia (MD, 0.65; 95% CI, 0.38–1.10), or desaturations (MD, 0.73; 95% CI, 0.32–1.68). Conclusion: The pooled evidence indicates that the combination measures may serve as an evidence-based guideline for pain relief among patients having minor pain. Besides, it also indicates that OS combined with NNS can be an alternative for better prevention and management of procedure pain in NICU newborns. Nevertheless, the results may be limited due to incomplete data, and thus, more randomized controlled trials or well-designed studies are required to determine the effects of OS+NNS in the future.